Land and schooling: transferring wealth across generations - Quisumbing, Agnes R.; Estudillo, Jonna P.; Otsuka, Keijiro (International Food Policy Research Institute, 2004)
"The authors address questions such as: (1) how do parents allocate land and education between sons and daughters? (2) how do changing returns to land and human capital affect parents' investments in children? (3) what do gender differences in land and schooling mean for the welfare of men and women? (4) is gender equity compatible with efficiency and growth? The book is based on intensive household surveys in Ghana, Indonesia, and the Philippines." -- From Text